1981
DOI: 10.1002/1097-4679(198101)37:1<192::aid-jclp2270370140>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of visual-spatial learning and memory in chronic alcoholics

Abstract: Administered the Memory‐for‐Designs Test and a verbal and Visuospatial paired associate learning test to separate groups of alcoholics (N = 32) 3 and 11 weeks abstinent from alcohol and to a matched control group (N = 16). Alcoholics were not impaired in verbal learning. Alcoholics 3 weeks abstinent performed significantly less well than controls on all nonverbal tasks and less well than 11‐weeks alcoholics on one nonverbal measure. No significant differences were found between 11‐week alcoholics and controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
2
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 13 publications
5
30
2
2
Order By: Relevance
“…Sullivan Leber, Jenkins, & Parsons, 1981;Mann, Gunther, Stetter, & Ackermann, 1999;Pitel et al, 2009;Rosenbloom et al, 2004;Rourke & Grant, 1999;Yohman, Parsons, & Leber, 1985) (for reviews, see Oscar-Berman et al, 2014;Pitel, Eustache, & Beaunieux, 2014). Remaining to be established are parameters of recovery, including length of sobriety, age at alcoholism initiation, age at testing, style of drinking, concomitant nutritional deficiencies and non-alcohol drug use, sex, physiological, ethnic, and genetic characteristics of alcoholics (Stavro et al, 2013).…”
Section: Recovery Of Component Processes Of Memory Functions With Alcmentioning
confidence: 99%
“…Sullivan Leber, Jenkins, & Parsons, 1981;Mann, Gunther, Stetter, & Ackermann, 1999;Pitel et al, 2009;Rosenbloom et al, 2004;Rourke & Grant, 1999;Yohman, Parsons, & Leber, 1985) (for reviews, see Oscar-Berman et al, 2014;Pitel, Eustache, & Beaunieux, 2014). Remaining to be established are parameters of recovery, including length of sobriety, age at alcoholism initiation, age at testing, style of drinking, concomitant nutritional deficiencies and non-alcohol drug use, sex, physiological, ethnic, and genetic characteristics of alcoholics (Stavro et al, 2013).…”
Section: Recovery Of Component Processes Of Memory Functions With Alcmentioning
confidence: 99%
“…Algunos estudios (cfr. Yohman y Parsons, 1985) constatan este déficit, pero otros no consiguen replicar estos hallazgos (Brandt, Butters, Ryan y Bayog, 1983;Riege, Tomaszewewski, Lanto y Metter, 1984), o los encuentran solamente durante las primeras semanas de abstinencia (Leber, Jenkins y Parsons, 1981).…”
Section: Memoria Visualunclassified
“…Investigators have widely reported that ventricular and sulcal enlargement documented in alcoholics with magnetic resonance imaging (MRI) can similarly ameliorate with abstinence, suggesting a brain structural basis for the neuropsychological deficits (Pfefferbaum et al, 1995(Pfefferbaum et al, , 1998. Despite documented improvements with long-term abstinence (Leber et al, 1981;Reed et al, 1992), most alcoholics demonstrate mild to moderate deficits in verbal, abstracting/problem-solving, learning/memory, and perceptual motor functions for extended periods after detoxification (Parsons, 1993). These deficits may represent either largely irreversible neurocognitive consequences of drinking or antecedents of alcohol abuse.…”
mentioning
confidence: 99%